2022
DOI: 10.1177/10781552221107548
|View full text |Cite
|
Sign up to set email alerts
|

Using an online journal club to improve Asian speakers’ comfort in using English to discuss and understand research papers written in English

Abstract: Introduction This study aimed to evaluate the participants’ comfort in understanding research papers written in English and discussing such research in English via an Asian online journal club. Methods A self-administered online survey was delivered to seven journal club meeting attendees from July 2020 to July 2021. A customer satisfaction analysis was performed to assess the association between the participants’ perspectives on program logistics and satisfaction. Results The recovery rate was 37.0% (44/119).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Thus, providing training opportunities for pharmacists already engaged in clinical settings is also essential. Journal clubs have been shown to positively impact pharmacists' clinical services, such as drug information services, patient counseling, and multidisciplinary rounds 19 . Notably, although not statistically significant, more pharmacists who graduated from 6‐year programs displayed more negative attitudes toward EBM in this study.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Thus, providing training opportunities for pharmacists already engaged in clinical settings is also essential. Journal clubs have been shown to positively impact pharmacists' clinical services, such as drug information services, patient counseling, and multidisciplinary rounds 19 . Notably, although not statistically significant, more pharmacists who graduated from 6‐year programs displayed more negative attitudes toward EBM in this study.…”
Section: Discussioncontrasting
confidence: 50%
“…Previous studies have demonstrated that self‐assessed EBM skills can be improved by attending EBM sessions, journal clubs, and hands‐on database searching sessions 12,14–18 . Although nearly 90% of Japanese pharmacists identified English proficiency as the barrier to EBM, Tsuchiya and colleagues reported that a participation in journal club tailored for Asians effectively improved understanding and critical appraisal skills of research papers written in English 19 . Therefore, development of EBM skills remains feasible despite language barriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation